Hairpin impacted in the duodenum of a 4-month-old child - a rarity - Rattan, Kamal Nain; -, Priyadarashani; Baridabad, Omkarmanik; Yadav, Kuldeep Kumar; Chopra, Bhavna (Indian Journal of Child Health, 2017)
Foreign body ingestion is common in children. The accidental ingestion is usually seen in children due to lingual curiosity. Most of the foreign body passes spontaneously through gastrointestinal (GI) tract; hence, requiring no removal. This is a case of impacted hairpin in the duodenum of a 4-month-old female child who accidentally ingested hairpin and was asymptomatic initially for 1 month and later presented with melena requiring surgical removal of hairpin. We failed to find in literature impacted hairpin in the duodenum associated with GI bleeding.